Avaliação em profundidade do Instituto Federal do Ceará: o Campus Baturité e sua relação com a inserção das juventudes no mundo do trabalho - Oliveira, Cristiane Gonzaga (2023)
This research aims to evaluate the insertion of youths in the world of work and as a locus of study the Instituto Federal do Ceará (IFCE), campus Baturité. To this end, an evaluative study is developed from the theoretical-methodological perspective and counter hegemonic policy of the field of evaluation, this is understood an epistemological category, the In-Depth Assessment (AP). This option was chosen because it provides an understanding of the context of public policy formulation, its content, its institutional trajectory, as well as the temporal and territorial spectrum. In this direction of theoretical-methodological triangulation, in-depth evaluative research, the most diverse techniques and instruments are used to unveil the object, and thus the view of the different agents of public policy is considered. Youth and Work were taken as founding theoretical categories and Professional and Technological Education (EPT) was used as a reference, understood in an intrinsic relationship with the Brazilian social and economic formation. In this sense, the analysis of the trajectory of Professional Education was carried out, from its emergence to the present day, in which its main transformations over time are outlined. In the context of this contextualization, the intricacies of the Federal Network of Professional, Scientific and Technological Education (RFEPCT), more specifically of the Federal Institute of Ceará, which makes up this network, are analyzed, regarding its legal and institutional framework. From the perspective of an in-depth evaluation, it is discussed how the IFCE campus Baturité acts to provide an education that declares human emancipation as its guideline, beyond mere qualification for the job market. This contradiction is presented by its creators in the face of what is carried out on a daily basis. Throughout the text, an analytical approach is developed about the trajectory of the graduates of the IFCE campus Baturité in order to reflect on their insertion in the world of work. It focuses mainly on how these young people see themselves in terms of issues related to work and education. It also starts with an understanding of youths to present their diversity, not being restricted to just one age group, thus seeking to understand these youths in their heterogeneity. In this sense, we can see the difficulties faced by these young people who graduated from the IFCE campus Baturité in order to enter the job market and remain there. And it also stands out how the institution helps and monitors this, through the Graduate Monitoring Program (PROAE).